Dynamic stress‐stiffening of carbon black‐filled vulcanizates. Issue 9 (28th June 2019) - Zhang, Yuanhong; Wang, Baojin; Zhang, Lin; Zhou, Hongbin
Abstract : Dynamic stress‐stiffening was investigated under relatively low deformation for the vulcanizates reinforced with carbon black. When dynamic strain sweep with fixed strain amplitude was imposed on samples, storage modulus and loss modulus were significantly increased and loss tangent and loss compliance remained unchanged. It was found that stress‐stiffening effect showed a strong dependence on aging time, frequency, as well as oscillatory strain magnitude. At 60°C, the strain‐aged vulcanizate produced a significant stress‐stiffening effect whereas the material hardening was not observed at 0°C. The increased Payne effect after cyclic deformations can be destroyed partially by dynamic strain sweeps. These features are quite different from the Mullins effect and dynamic stress‐softening effect in filled rubbers. We interpreted this character of filled vulcanizates in much developed carbon black agglomerates and other possible superstructures. The results provide new insight into understanding the relationship between the rolling resistance of tires and lab‐tested dynamic property. POLYM. ENG. SCI., 59:1743–1752, 2019. © 2019 Society of Plastics Engineers